A new closed-form algorithm for 3-D single near-field source. Issue 4 (1st October 2020) - Li, Wanchun; Ma, Yezi; Wang, Min; Guo, Yuning; Li, Yingxiang
ABSTRACT: Recently, a single source location problem has attracted special attention in many previous works. A method was lately proposed to estimate three-dimensional (3-D) parameters (i.e. range, azimuth angle, elevation angle) for single source using a geometry restriction-free Uniform Circular Array (UCA), whereas it required a strong presupposition. In this letter, considering the problem of estimating 3-D parameters of a single near-field source, we expand the signal model to a generalised one based on the previous work. This expansion is more available to common situations including near-field condition. In addition, in contrast to the previous work, the proposed method is shown to be more accurate and computationally efficient. Numerical simulations are provided to verify the performance of the proposed method.